Activity Workflow in the Process of Article Publication and Quality Control in the Journal Acta Stomatologica Croatica - Hrvoje Brkić (University of Zagreb. School of Dental Medicine, 2017)
During the last fifty years the Editorial board of Acta Stomatologica Croatica (ASCRO) has tried to increase journal's quality by introducing quality control in all phases of article editing from the submission to the final publication. We tried to follow the procedures and trends of indexed journals in biomedicine, hereby succeeding in acceptance of ASCRO in six international index databases and the greatest citation database SCOPUS. This article represents the activity workflow for every submission to the journal, from the beginning until the final publication. Average time from submission to publication is three months.